Penerapan pendekatan realistic mathematics education (rme) untuk meningkatkan kemampuan numerasi siswa pada materi pecahan kelas V sekolah dasar - Aspirawati Juniar; Hasan Mahfud; Matsuri Matsuri; Anesa Surya (Universitas Sebelas Maret, 2024)
This research aims to improve the numeracy skills of fifth grade students at SD 2 Pelem through the application of Realistic Mathematics Education approach. Classroom Action Research (CAR) is a type of research. Each cycle contains the stages of planning, implementation, observation and reflection. The research subjects were 18 students and teachers. Data collection techniques used are observation, interviews, documentation and tests. Data validity testing techniques use source triangulation and engineering triangulation. Data analysis technique uses interactive data analysis techniques with Miles and Huberman model. The research results show that applying RME approach can improve students' numeracy skills. This is proven by the average numeracy test score obtained by students in pre-action of 56.17 with classical completion of 16.67%. Cycle I obtained an average of 75.78 with classical completeness of 66.67%. Cycle II obtained an average of 88.67% with classical completeness of 99.44%. Based on the research results, it can be concluded that the application of the RME approach can improve the numeracy skills of class V students. This research adds scientific insight into the application of RME approach, this research also contributes to providing teachers with insight into implementing RME approach, especially in mathematics learning.